Drawings and Scale Models Used in Building the Spanish Royal Sites (diségno, 2018)
In 1545 Emperor Charles V created the Board of Works and Forests to define and control all the building projects promoted by the Crown. As a result, the administration of the royal estates was updated and modernised due to its pyramidal structure. The building works were supervised by architects or draftsmen, who were responsible for the project’s definition and construction respectively. The latter should also define the building contracts and build the models to be used by craftsmen. Following completion of the construction work, the administration of the royal site was entrusted to a governor or alcaide, so that the building process and management were distinctly separated. King Philip II transformed the previous practices into a strict regulatory framework affecting every craftwork, and defining in detail each piece of work in the building contracts. They included frequent references to moulds and models, and even sketches. Accordingly, the main targets and original contributions of our researtch are: 1/ to link the graphic documents to the written building contracts in order to make evident their complementary role, what will permit to know under which circumstances they were produced; 2/ to extend the research subject to every craftwork in the palace’s construction, and not just to the stonework; 3/ to diffusesuch an interesting set of documents that is essential to the history of construction in the 16th century, and particularly to the history of the royal works. For this purpose we publish for the first time some of these documents and drawings.
Keywords: Drawings,; Models,; Royal Sites; History of Construction; 16th Century